China abroad : travels, subjects, spaces - Ho, Elaine Yee Lin; Kuehn, Julia (Hong Kong University Press, 2009)
This collection brings together texts and cross-cultural experiences of modern Chinese travellers, recent migrants and diasporic Chinese in a number of global locations. It illustrates how movements across cultures have shaped the ways in which 20th-century China and Chineseness have been imagined and represented.